Economic Growth in Central Java: Does Manufacturing Industry Agglomeration Matter? - Benny Imantria (Diponegoro Journal of Economics, 2024)
The manufacturing industry agglomeration in Central Java has experienced growth and has played an important role in increasing production efficiency. However, Central Java's contribution to Indonesia's GDP (GRDP) has declined, indicating early signs of deindustrialization. This study aims to identify manufacturing industry agglomeration and its effect on economic growth in Central Java. The data sample consists of 490 observations from 35 districts/cities during the period 2010-2023, analyzed using panel data regression with a fixed effects model. This study presents a novelty in the form of independent variables representing distribution and consumption aspects, as well as a more recent and extended observation period. The study found that medium-level manufacturing industry agglomeration occurs only in Jepara, while low-level manufacturing industry agglomeration occurs in Kudus, Pekalongan, Pekalongan City, Purbalingga, Sukoharjo, Semarang, Klaten, Batang, Kebumen, Karanganyar, Salatiga City, Surakarta City, Semarang City, Temanggung, and Boyolali. Manufacturing industry agglomeration has a non-significant positive effect on economic growth, while gross fixed capital formation (GFCF), labor force, average years of schooling, capital expenditure, and minimum wage have a significant positive effect on economic growth. Policymakers are encouraged to promote further manufacturing industry agglomeration and provide public goods that support both manufacturing industry agglomerations and economic growth.